Study on hypercompact and lightweight data logger separators for wild animals. (17th January 2021) - Abe, Takuma; Kubo, Natsumi; Abe, Kazuki; Suzuki, Hirokazu; Yoda, Ken; Tadakuma, Riichiro; Tsumaki, Yuichi
Abstract : In ecology and ethology, a technique called 'bio-logging' has been used to record the behaviour of wild animals by attaching a small logger, which includes a global positioning system (GPS) or acceleration sensor, to the animal of interest. This method's disadvantage is that the recovery of the logger is inefficient. In this study, we propose a data logger separator, which solves this problem by focussing on the logger recovery method. The device, which weighs ∼10 g, is intended for use on a shallow-diving seabird such as gulls. It comprises a separation mechanism based on a rotary key to achieve quiet separation and avoid causing stress to the seabird and the surrounding individuals. Moreover, the device is equipped with a wireless microcomputer that can be separated via a remote control from a distance of ∼100 m. For separation experiments on stuffed birds, the separation performance was confirmed to be sufficient. Because of experimentally testing the device in a real environment with low temperatures and wet conditions, it was considered that the separator's performance was sufficient to allow it to be used practically in the wild. GRAPHICAL ABSTRACT: UF0001